Calpain‐mediated cleavage of DARPP‐32 in Alzheimer's disease. Issue 5 (14th July 2015) - Cho, Kwangmin; Cho, Mi‐Hyang; Seo, Jung‐Han; Peak, Jongjin; Kong, Kyoung‐Hye; Yoon, Seung‐Yong; Kim, Dong‐Hou
Summary Toxicity induced by aberrant protein aggregates in Alzheimer's disease (AD) causes synaptic disconnection and concomitant progressive neurodegeneration that eventually impair cognitive function. cAMP‐response element‐binding protein (CREB) is a transcription factor involved in the molecular switch that converts short‐term to long‐term memory. Although disturbances in CREB function have been suggested to cause memory deficits in both AD and AD animal models, the mechanism of CREB dysfunction is still unclear. Here, we show that the dopamine‐ and cAMP‐regulated phosphoprotein 32 kDa (DARPP‐32), a key inhibitor of protein phosphate‐1 (PP‐1) that regulates CREB phosphorylation, is cleaved by activated calpain in both AD brains and neuronal cells treated with amyloid‐β or okadaic acid, a protein phosphatase‐2A inhibitor that induces tau hyperphosphorylation and neuronal death. We found that DARPP‐32 is mainly cleaved at Thr153 by calpain and that this cleavage of DARPP‐32 reduces CREB phosphorylation via loss of its inhibitory function on PP1. Our results suggest a novel mechanism of DARPP‐32–CREB signalling dysregulation in AD.